Social Variation in Menarcheal Age in Big-City Girls from Upper Silesia in 1981 - Waliszko, Anna; Hulanicka, Barbara; Bielicki, Tadeusz (Anthropological Review, 1987)
In a sample of 19 409 schoolgirls from the three largest cities of the Upper Silesia conurbation, Southern Poland, menarcheal age was studied in relation to several social variables. Mean menarcheal ages for girls from different occupational groups (father’s occupation) range from 12.82 to 13.30 years and form the following sequence, in increasing order: menagers-police-non technical professionals – engineers – technicians and foremen- skilled industrial workers and small businessmen – unskilled workers – coal miners. Mean menarcheal age for an occupational group is strongly dependent upon the group’s rank in socio-economic status, the latter being defined by the mean of the group’s rank in parental education, family income per capita, family size and dwelling conditions. However, daughters of men in the police force mature significantly earlier and daughters of coal miners significantly later, than would be expected from each group’s rank in socio-economic status. The occupational gradient in menarcheal age tends to persist even when other social variables are statistically controlled, eg. when analysis is limited only to families with no more than two children or to those with fathers of city background only. There is interaction between family size and occupational status: menarche in girls from small families tends to occur earlier than those from larger families but this effect is strongest among professionals, weaker among skilled manual workers and absent among unskilled workers. Menarcheal age tends to increase with decreasing parental education, although the gradient is not steep. When families below a certain level of economic standing are discarded from the best educated and the least-well educated groups mean menarcheal age decreases in each group but surprisingly, much more dramatically in the former than in the latter: this suggests than parents of higher educational status make more rational use of the resources which they have at their disposal.